Mechanical properties and energy absorption of composite bio-inspired multi-cell tubes. (March 2023) - Wu, Fei; Chen, Yating; Zhao, Shunqiu; Hong, Yihao; Zhang, Zhengrong; Zheng, Shiwei
Abstract: New composite bio-inspired multi-cell metal tubes—lotus root inspired structures (LR-IS), lotus root-horsetail inspired structures (LR-HS1 and LR-HS3) and lotus root-honeycomb inspired structures (LR-HC1 and LR-HC2) — were proposed and fabricated by selective laser melting. Their mechanical behaviors and energy absorption characteristics were investigated under the axial, radial and three-bending crushing via experiments and numerical simulation. Their crushing force efficiency values ranged from 0.8–1.0, which were much higher than that (0.536) of metal thin-walled hollow tubes (HT). The specific energy absorption values in axial, radial and three-point bending directions were 27.7–81.0 J/g, 1.5–12.3 J/g and 0.8–10.7 J/g, respectively, which were approximately 2-13 times of HT. Compared with the HT, the structural strength, rigidity, energy absorption, crushing force efficiency and specific energy absorption of the bionic composite metal tubes were greatly improved in axial, three-point bending and radial directions. Their axial directions were the main directions of energy absorption and collision avoidance, and the lateral directions had sufficient load bearing capacity. These bionic multi-cell tubes have the potential to be used as lightweight, rigid, high strength, impact-resistant, and energy-absorbing independent energy absorbers. Highlights: Three kinds of composite bio-inspired multi-cell metal tubes are introduced in this paper. Explore mechanical behavior and energy absorption of bionic multi-cell tubes. Explore the effect of different bionic structural combination forms on mechanical behavior and energy absorption. Interaction effect analysis of bionic multi-cell tubes under axial quasi-static loading.